Impact of Lesion Length on Functional Significance in Intermediate Coronary Lesions. Issue 3 (6th November 2012) - Iguchi, Tomokazu; Hasegawa, Takao; Nishimura, Satoshi; Nakata, Shinji; Kataoka, Toru; Ehara, Shoichi; Hanatani, Akihisa; Shimada, Kenei; Yoshiyama, Minoru
Abstract Background: Myocardial fractional flow reserve (FFR) is useful in the evaluation of coronary lesion ischemia. However, the impact of lesion length on FFR has not been adequately assessed. Hypothesis: We hypothesized that lesion length would influence functional significance in intermediate coronary lesions. Methods: FFR measurements were assessed in 136 patients (163 lesions) with stable angina who had >40% stenotic coronary lesion by quantitative coronary angiography (QCA). One hundred sixty‐three lesions were classified as intermediate (40%–70% stenosis; n=107; group I) or significant (≥70%; n=56; group S) by QCA. We assessed the relationships between lesion length, coronary stenosis, and FFR in these 163 lesions. Results: Regression analysis revealed an inverse correlation between the percentage of diameter stenosis (%DS) and FFR in group S (r = −0.83, P < 0.0001). In group I, no significant correlation was found between %DS and FFR (r = −0.06, P = 0.55), whereas lesion length was significantly inversely correlated with FFR (r = −0.79, P < 0.0001). Receiver operating characteristic curve analysis demonstrated that the best cutoff value for predicting an FFR value <0.80 was a lesion length >16.1 mm in group I (sensitivity, 86%; specificity, 94%). Conclusions: These study findings suggest that lesion length has a physiologically significant impact on intermediate‐grade coronary lesions. Clin. Cardiol. 2011 DOI: 10.1002/clc.22076 The authors have no funding, financial relationships, or conflicts of interest to disclose.